Four virally determined nuclear antigens are expressed in Epstein-Barr virus-transformed cells. - Kallin, B (1986)
The expression of Epstein-Barr virus (EBV)-determined antigens associated with growth-transformation of B cells was studied by immunoblotting with human sera from healthy donors. Four antigens were detected in EBV-carrying cell lines and in B lymphocytes early after infection with the transforming B95-8 substrain of virus. They were not found in uninfected cells, nor could they be demonstrated with sera lacking antibodies to EBV antigens. All four antigens were nuclear. Each of them varied in size in the different cell lines. The two antigens with the lowest molecular weight were identified as EBV-determined nuclear antigens (EBNAs) 1 and 2. The two high molecular weight antigens (140-160 kDa and 150-180 kDa, respectively) were detected with 6 of 16 EBV antibody-positive sera. These proteins appeared to be antigenically unrelated to each other and to EBNAs 1 and 2 and were designated EBNAs 3 and 4. Like EBNAs 1 and 2, they bound to double- and single-stranded DNA in vitro.